Debris flows in the central sector of the northern slopes of the Main Caucasus Ridge: peculiarities of the current situation (Journal of Nepal Geological Society, 2016)
This paper provides examples of real events of debris flows in the 21st century. The analysis of the debris flows reveals that there is a variety of manifestation of debris flow processes and triggering factors. It also demonstrates the lack of prospects for the modern trend of creating a single model for forecasting the occurrence, development, impacts and parameters of debris flows that would be equally suitable for other phenomena of gravitational nature such as avalanches, landslides or rock falls. Moreover, it shows that the monitoring is unrepresentative, which is unacceptable, and demonstrates the often lack of hydro-meteorological data on mountainous areas.